Cita sin límites con Emilio Prados - Hernandez Pérez, Patricio (Huarte de San Juan. Filología y Didáctica de la Lengua, 2012)
On the 50th anniversary of the death in exile of the poet Emilio Prados, born in Malaga and a member of the Generation of 27, we do an assessment and a tour of his poetry from the vantage point of his last unfinished book, Cita sin límites. This book is a diary of his last days and is summarizing his poetry work.
Keywords: Spanish Generation of 27; Emilio Prados; poetry and philosophy